The theology of the later Pauline letters - Lincoln, Andrew T. (New Testament theology, 2007)
This volume investigates the respective theologies of the Letters to the Colossians and the Ephesians, and in so doing provides an accessible introduction to the themes and significance of these New Testament books. A. J. M. Wedderburn examines the background to Colossians, and considers both its readers' situation and that of its author. He asks whether the proponents of the teaching against which this letter is written were Christians, putting forward their views as the true form of Christianity (as in Galatia), or whether they existed outside the Christian community as a seductive alternative to it. Andrew T. Lincoln examines in turn the authorship of Ephesians, and tries to explain the letter's strategy of persuasion and the key elements of its teaching about the new identity of the Christian believer. The similarities and differences between the thought of Ephesians and that of Paul are thereby set out clearly. Both sections of the book reflect on the relevance of these letters for today.